Singapore : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2004)
Singapore's financial sector, which is dominated by the banking sector, remains robust despite a series of economic downturns and substantial asset price declines. Economic developments in the past few years have highlighted Singapore's vulnerability to exogenous shocks, including the outbreak of Severe Acute Respiratory Syndrome (SARS). Systemic liquidity is well managed. Singapore has proactively implemented significant financial sector reforms since 1998. Although it has undergone major structural changes in recent years, Singapore's financial sector is still dominated by the banking industry.